2020
DOI: 10.4025/actascianimsci.v42i1.48734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibiotic replacement with garlic powder and probiotic on performance, carcass characteristics, oxidative enzymes and intestinal morphology of broiler chickens

Abstract: An experiment was conducted to evaluate the effects of probiotic and garlic powder instead of antibiotic on performance, carcass characteristics, oxidative enzymes and intestinal morphology of broiler chickens. A total of 200 one-day-old male broiler chicks were used in a completely randomized design. The experimental groups were including control group (without any additives) or CG, antibiotic group or AG, garlic powder group or GG, probiotic group or PG and garlic powder plus probiotic group or GPG. The broi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…The width of villi and the depth of crypts and the thickness of the duodenal mucosa were increased in piglets receiving garlic extract, whereas piglets receiving 2 ml of the extract performed better (Tatara et al, 2008). Dried garlic fed to Ross 308 chicks from the first day post hatch increased the height of villi in the duodenum, jejunum and ileum compared to the control group, and increased the width of villi in the ileum (Rastad, 2020). Positive effects on the width and number of villi were also observed for piglets receiving allicin.…”
Section: Herbal Active Substancesmentioning
confidence: 83%
See 1 more Smart Citation
“…The width of villi and the depth of crypts and the thickness of the duodenal mucosa were increased in piglets receiving garlic extract, whereas piglets receiving 2 ml of the extract performed better (Tatara et al, 2008). Dried garlic fed to Ross 308 chicks from the first day post hatch increased the height of villi in the duodenum, jejunum and ileum compared to the control group, and increased the width of villi in the ileum (Rastad, 2020). Positive effects on the width and number of villi were also observed for piglets receiving allicin.…”
Section: Herbal Active Substancesmentioning
confidence: 83%
“…It was also found that while antibiotics were not found to affect the thickness of the mucous layer in the guts, the villous surface area was increased in the jejunum, and goblet cell density was greater in the jejunum and ileum. An administration of virginamycin to Ross 308 chicks for 42 days increased the height and width of the villi in the duodenum, jejunum and ileum compared to the control group (Rastad, 2020).…”
Section: Antibioticsmentioning
confidence: 83%
“…Eidi et al (2006) found that garlic improved lipid profiles and reduced serum AST levels. The use of garlic powder and probiotics, according to Rastad (2020), greatly reduced the activity of liver enzymes, including AST, ALT, and ALP. Also, Alagawany et al (2015) found that dietary supplementation of garlic in the diet increased SOD activity.…”
Section: Resultsmentioning
confidence: 99%
“…A study that examined the antioxidant and antibacterial effects of comparable concentrations of fresh garlic (FG), GP, and garlic oil (GO) on lipid oxidation and microbiological growth in raw chicken sausage stored at 3 • C found that the addition of FG (30 g/kg) or GP (9 g/kg) greatly lowered the aerobic plate count and thereby extended the shelf-life of the product to 21 days, whereas the addition of GO or butylated hydroxyanisole had similar results to the control (Sallam et al, 2004). Another study examined the impact of probiotics and garlic powder (GG) instead of antibiotics on broiler chicken performance, carcass parameters, oxidative enzymes, and intestinal morphology (Rastad, 2020). In that work, 200 one-day-old male broiler chicks were allotted to five treatments in a completely randomized design: control group (no additives) or CG, antibiotic group or AG, GG group, probiotic group or PG, and GP plus probiotic group GPG.…”
Section: Natural Antimicrobialsmentioning
confidence: 99%